Chemical, sensory and consumer analysis of cork taint in South African wines - Van Eeden, Petrus Rabe (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc Food Sc (Food Science))--University of Stellenbosch, 2009.